Berberine: A Perspective Compound in the Development of New Medicines - Thi Duong, Thuan; Thi Hai Yen, Tran; Thanh Hai, Nguyen; Heinämäki, Jyrki; Thi Minh Hue, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
Berberine (BBR) is a plant-origin alkaloid with a long history, commonly used for treating infectious diarrhea. In recent years, BBR has been found with many pharmacological effects such as lowering blood glucose, anti-hyperlipidemia, liver protection, kidney protection, anti-atherosclerosis, antioxidants, etc. However, several studies revealed that the oral bioavailability of BBR was very low. Therefore, drug delivery systems have been studied to improve the absorption of BBR through an intestinal epithelial barrier such as liposomes, proliposomes, phytosomes, and nano lipids. The finding of new drug delivery systems has great potential in developing new medicines with a traditional active substance – BBR. Besides, BBR is also an important lead compound with different pharmacological effects, promising to form many new drug discovery programs with high feasibility.